Dosimetric study of GZP6 60Co high dose rate brachytherapy source. (28th May 2018) - Lei, Qin; Xu, Anjian; Gou, Chengjun; Wen, Yumei; He, Donglin; Wu, Junxiang; Hou, Qing; Wu, Zhangwen
Abstract: The purpose of this study was to obtain dosimetric parameters of GZP6 60 Co brachytherapy source number 3. The Geant4 MC code has been used to obtain the dose rate distribution following the American Association of Physicists in Medicine (AAPM) TG‐43U1 dosimetric formalism. In the simulation, the source was centered in a 50 cm radius water phantom. The cylindrical ring voxels were 0.1 mm thick for r  ≤ 1 cm, 0.5 mm for 1 cm <  r  ≤ 5 cm, and 1 mm for r  > 5 cm. The kerma‐dose approximation was performed for r  > 0.75 cm to increase the simulation efficiency. Based on the numerical results, the dosimetric datasets were obtained. These results were compared with the available data of the similar 60 Co high dose rate sources and the detailed dosimetric characterization was discussed.